2004
DOI: 10.1001/archotol.130.3.353
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Osteoporosis on Patients With Maxillofacial Trauma

Abstract: Background: Although maxillofacial injuries in the elderly population frequently result from falls and motor vehicle crashes, the association between osteoporosis and fractures of the maxillofacial region remains poorly defined.Objective: To evaluate the relationship between osteoporosis and maxillofacial trauma in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 23 publications
4
14
0
3
Order By: Relevance
“…In a study of 59 patients older than 60 years with osteoporosis, Werning et al found that osteoporosis predisposed elderly patients Plastic and Reconstructive Surgery • February 2016 to multiple facial fractures in low-impact and highimpact situations. 33 In addition, documented changes in expansion of paranasal cavity volume and progressive resorption of the maxillary alveolar ridge, especially in edentulous areas, can influence patterns of fracture. 34 Overall, the influence of osteoporosis and osteopenia on the craniofacial skeleton is unclear and deserves further study.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 59 patients older than 60 years with osteoporosis, Werning et al found that osteoporosis predisposed elderly patients Plastic and Reconstructive Surgery • February 2016 to multiple facial fractures in low-impact and highimpact situations. 33 In addition, documented changes in expansion of paranasal cavity volume and progressive resorption of the maxillary alveolar ridge, especially in edentulous areas, can influence patterns of fracture. 34 Overall, the influence of osteoporosis and osteopenia on the craniofacial skeleton is unclear and deserves further study.…”
Section: Discussionmentioning
confidence: 99%
“…It likely results from the combined functional consequences of aging, systemic pathologies and the use of psychotropic drugs. Furthermore, elderly patients with osteoporosis more likely develop maxillofacial fractures following low-impact trauma (8), implying that osteoporosis is a risk factor for the development of maxillofacial fractures.…”
Section: Discussionmentioning
confidence: 99%
“…While some authors reported a progressive decrease of mandibular bone mineral density (BMD) with age [10], other could confirm a higher mineral content in the mandibles of old patients, what was interpreted as a response to atrophy after tooth loss [11,12]. Some studies suggest an influence of osteoporosis in the fracture incidence in the maxillofacial area [13,14].…”
Section: Introductionmentioning
confidence: 99%